Abatacept in Psoriatic Arthritis: A Review. Issue 2 (June 2014) - Varada, Sowmya
Abatacept is a soluble, fully human, recombinant fusion protein composed of the extracellular domain of CTLA-4 and a modified Fc portion of IgG1. It is the first in a class of agents that competitively inhibit the interaction of cell surface CD28 with CD80/86 to modulate T lymphocyte costimulation and activation. Its success in treating moderate to severe rheumatoid arthritis and juvenile idiopathic arthritis has prompted its investigation for use in psoriatic arthritis. Many psoriatic arthritis patients fail tumor necrosis factor inhibitor therapy, highlighting the need for treatments with novel mechanisms of action. One phase I trial studying abatacept in psoriasis and one phase II trial in psoriatic arthritis have been published, with phase III trials under way. Results thus far have been promising, but the drug's long-term efficacy and safety profile are not yet known. This article reviews the agent's mechanism of action, efficacy, safety profile, and clinical potential in treating psoriatic arthritis.